Analisis Teori Pembelajaran Bruner Terhadap Berfikir Tingkat Tinggi Siswa Sekolah Dasar - Linda Juliharti; Yanti Fitria; Risda Amini (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
Abstract: Bruner's theory emphasizes that students learn through active engagement with concepts and principles in solving problems and teachers serve as motivators for students to gain experience that allows them to find and solve problems, in line with higher-order thinking which is the cognitive ability of learners at a higher level, that is, learners are able to combine facts and ideas in the process of analyzing, Evaluate to the stage of making an assessment of a fact learned. HOTS is a thought process of students at a higher cognitive level, namely problem-solving ability, creative thinking ability, critical thinking, argument ability, and decision-making ability. This research uses a literature study method with the aim of analyzing Bruner's theory in high-level thinking learning in elementary schools. Keywords: Bruner theory, higher order thinking, elementary school.